Challenges and Strategies of Multicultural Integration for Migrant Communities in Urban Areas - Gantulga, Erdene; Bataar, Otgon; Batzorig, Ulagan (Journal Social Civilecial, 2024)
This research focuses on the multicultural assimilation and how migrant groups perform this in urban areas; irregularities in urban migration have not been exhaustively researched on. In this study, a qualitative research method was conducted through semi structured interviews with 30 migrants from various backgrounds and participant observations in community settings. Among the observation, the impact of integration highlighted discrimination as a major factor, exclusion from many resources and socio-economic prejudice. Firstly, migrant lives in substandard accommodation, his/her children do not get education or only substandard, and the migrant cannot easily get a job. In addition, cultural adaptation was established as a multifaceted procedure and as processes of the identity formation related to attempts to overcome cultural divides. The study also notes the importance of social networks and participation in the integration processes to illustrate that systematic informal networks offer social, emotional, and material support to migrants discouraged by the urban environment. In achieving these objectives, the study fills gaps in the existing migration literature by describing how migrants engage with and modify the built environment. The conclusions underscore the need for intervention in practice to address problems associated with urban processes, which means implementing anti-essentialization of culture, on the one hand, and the diversification of resources, on the other, in order to have greater returns in the context of future demographic divides. They make a valuable input to ongoing debates around urban governance and social inclusion or exclusion in complex societies. Future studies should extend current research on the local government and other bottom-up community organizations in relation close to migrants’ assimilation.